The Impact of Competency-Based Human Resource Management on Organizational Competitive Advantage - Warsono, Heribertus Yudho; Sulistiyanto, Sulistiyanto; Kusuma, Emeralda Ayu (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study explores the impact of competency-based human resource management (CBHRM) on organizational competitive advantage. CBHRM emphasizes aligning employee competencies with organizational strategies to maximize human capital, improve performance, and strengthen competitive positioning. The research highlights key factors for the successful implementation of CBHRM, including a strong organizational culture that promotes continuous learning, leadership commitment, the development of competency frameworks, and ensuring employee understanding of required competencies. The findings suggest that while CBHRM offers significant potential for improving organizational effectiveness, its success depends on organizational context, leadership involvement, and the integration of these factors into the organizational culture. The study concludes that CBHRM, when implemented properly, can provide organizations with a sustainable competitive advantage, particularly in dynamic and competitive industries.